Development of Micro, Small and Medium Enterprises in Budo Tourism Village - Nancy Onibala; Rahma Alhasni; Anindya Puspita Putri; Max L. Tamon; Mujibur Rahman (Technium Social Sciences Journal, 2024)
The development of micro, small and medium enterprises (MSMEs) is very strategic, because the MSME sector has a strategic role in national economic development that absorbs labour, tax revenue and regional income and also plays a role in distributing development results. The existence and role of MSMEs should be a serious concern for the government, by making programmes that focus more on increasing competitiveness and sustainability. The focus of this research is the development of MSMEs through management and marketing systems in Budo tourism village. Tourism village is one form of implementation of community-based and sustainable tourism development. Tourism villages are one part of the tourism industry that also plays a role in the absorption of labour and the improvement of the welfare of rural communities. In other words, it can be an excellent tool in the socio-economic development of rural communities so that the flow of urbanisation can be reduced. Through the development of tourism villages, it is expected that there will be equalisation in accordance with the concept of sustainable tourism development. This article uses descriptive qualitative research methods. Data collection through observation, interviews, and documentation. The results of this study indicate that the development of MSMEs in Budo tourism village is still experiencing obstacles because the management of MSMEs is still being improved, and marketing of MSME products must be maximised.